2019
DOI: 10.1111/jcal.12333
|View full text |Cite
|
Sign up to set email alerts
|

Chinese undergraduate students' perceptions of mobile learning: Conceptions, learning profiles, and approaches

Abstract: Close links between students' conceptions of and approaches to learning were established in the past research. However, only a few quantitative studies investigated this relationship particularly with regard to mobile learning (m‐learning). The correlation between learners' conceptions and approaches to m‐learning was analysed using a partial least squares analysis applied to data obtained from a sample of 971 undergraduate students in China. The results indicated that students' conceptions of m‐learning could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…This finding echoed the importance of high-level conceptions of language learning on their online selfregulatory strategies (Chamot, 2018) and provided supports for the argument that learners in the groups of seeing in a new way and high commitment had greater positive perceptions of their online self-regulation (Tsai, 2004;Zheng et al, 2016). Characteristics were in accordance with the description of high engagement students by Lin, Deng, Hu and Tsai (2019). In contrast, the lower-level conceptions groups took a laissezfaire approach (Xiao, 2012) to construct online learning environment with ineffective time management and task strategies.…”
Section: The Significant Differences Among the Profiled Efl Learners supporting
confidence: 69%
“…This finding echoed the importance of high-level conceptions of language learning on their online selfregulatory strategies (Chamot, 2018) and provided supports for the argument that learners in the groups of seeing in a new way and high commitment had greater positive perceptions of their online self-regulation (Tsai, 2004;Zheng et al, 2016). Characteristics were in accordance with the description of high engagement students by Lin, Deng, Hu and Tsai (2019). In contrast, the lower-level conceptions groups took a laissezfaire approach (Xiao, 2012) to construct online learning environment with ineffective time management and task strategies.…”
Section: The Significant Differences Among the Profiled Efl Learners supporting
confidence: 69%
“…The responses to both the Likert-type items and the open-ended questions indicate that students have few problems accessing and understanding the screencasts. Students have been found to be comfortable with using technology and appreciate it when teachers use it (Lin et al 2019). However, instructors should make sure that all the students have working computers, internet access, and are able use them effectively.…”
Section: Discussionmentioning
confidence: 99%
“…An assignment will be posted on a learning management system (LMS), completed on a word processor, and submitted electronically. The students of today are more familiar with technology than previous generations, and they use technology in a variety of ways (Lin et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have indicated that mobile libraries can help learners gain knowledge, boost learning attitudes and facilitate cooperation and problem-solving skills (Lai and Hwang, 2014;Tu, 2018;Tu and Hwang, 2018). For instance, university students can solve their problems while using mobile libraries to support their activities; moreover, their activity attendance and learning performance can also be enhanced (Chookaew et al, 2015;Hwang et al, 2017;Lin et al, 2019;Wu et al, 2011).…”
Section: Literature Review 21 Mobile Librariesmentioning
confidence: 99%